THE ESSENCE OF CIVIL SOCIETY AND ITS FUNCTION IN MODERN CONDITIONS - Belokopytov D.V. (Pressing Problems of Public Administration, 2016)
Overview basic approaches to the analysis of civil society. It is proved that civil society has always advocated a dual form and consists, on the one hand, the public-political component, on the other hand - the private component. The basic functions of civil society. It is shown that civil society should be seen not only in the passive sense – a network of public institutions and structures - but also active - in the context of collective actors.